A monolithic immersion metalens for imaging solid-state quantum emitters - Tzu-Yung Huang (Nature Portfolio, 2019)
Photon collection from quantum emitters is difficult, and their scale requires the use of free-space optical measurement setups which prevent packaging of quantum devices. Here, the authors design and fabricate a metasurface that acts as an immersion lens to collect and collimate the emission of an individual emitter.